2011
DOI: 10.1038/eye.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of diabetic retinopathy: fenofibrate and ACCORD Eye studies

Abstract: The approach of all ophthalmologists, diabetologists and general practitioners seeing patients with diabetic retinopathy should be that good control of blood glucose, blood pressure and plasma lipids are all essential components of modern medical management. The more recent data on the use of fenofibrate in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) and The Action to Control Cardiovascular Risk in Diabetes (ACCORD) Eye studies is reviewed. In FIELD, fenofibrate (200 mg/day) reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 42 publications
2
42
1
1
Order By: Relevance
“…1 As the most common microvascular complications of diabetes mellitus (DM), they are also increasingly becoming a major cause of blindness in low-and middle-income countries (LMICs) as DM prevalence and incidence in these settings have risen sharply in recent years. 2 Although the development of sight-threatening complications of DM can be delayed by appropriate treatment of systemic diseases such as DM itself, high blood pressure and lipid metabolism abnormalities, 3 nearly all type 1 DM patients and 60% type 2 patients develop DR or DMac. 4 If the disease progresses to a stage where direct intervention is necessary, laser treatment or intravitreal injection of steroid or antivascular endothelial growth factor (anti-VEGF) agents are often successful in preserving vision.…”
Section: Special Sectionmentioning
confidence: 99%
“…1 As the most common microvascular complications of diabetes mellitus (DM), they are also increasingly becoming a major cause of blindness in low-and middle-income countries (LMICs) as DM prevalence and incidence in these settings have risen sharply in recent years. 2 Although the development of sight-threatening complications of DM can be delayed by appropriate treatment of systemic diseases such as DM itself, high blood pressure and lipid metabolism abnormalities, 3 nearly all type 1 DM patients and 60% type 2 patients develop DR or DMac. 4 If the disease progresses to a stage where direct intervention is necessary, laser treatment or intravitreal injection of steroid or antivascular endothelial growth factor (anti-VEGF) agents are often successful in preserving vision.…”
Section: Special Sectionmentioning
confidence: 99%
“…Furthermore, improved control of hypertension in the UKPDS reduced progression of diabetic retinopathy by 34% [6]. In this study, the risk of microvascular complications in T2DM was shown to be associated independently and additively with hyperglycemia and hypertension, with risk reductions of 37% per 1% decrement in HbA1C and 11% per 10 mm Hg decrease in systolic blood pressure [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…A surprising result of the study was the failure to demonstrate a significant effect of intensive blood pressure control (SBP<120 mmHg) on the progression of retinopathy [7]. It is possible that the median systolic pressure of 133 mm Hg in the non-intensive treatment group was an effective level for preventing progression or that the duration of follow-up was insufficient [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…На наш погляд, це може відбуватися за рахунок ліпідомодифікуючих та антизапальних влас-ти востей фенофібрату, який також має здатність блокувати синтез ферменту -альдо-зоредуктази, відновлювати ендотелій та активувати ядерні рецептори PPAR-α. Важ-ливою властивістю фармакологічної дії ос-нов ної речовини препарату також вважають здат ність блокувати синтез VEGF-фактора та зменшувати активність проліферативних про цесів у сітківці ока [12,13]. Тобто пози-тивна динаміка перебігу ДР з проявами ДМН у хворих на ЦД 2-го типу за оцінкою по казників гостроти зору, ТСМД та ліпідних фракцій сироватки крові в умовах тривалого прийому мікронізованого фенофібрату, може відбуватися під його позитивним впливом на важливі ланки патогенезу ДР, що забезпечило необхідні передумови для відновлення важливих процесів життєдіяльності клітин сітківки.…”
Section: результати та їх обговоренняunclassified